Thermal hydraulic analysis of a PWR loaded with annular fuel rods - Wallen Ferreira De Souza; Maria Auxiliadora Fortini Veloso; Antonella Lombardi Costa; Clubia Pereira (Brazilian Journal of Radiation Sciences, 2021)
In 2006, the final report of the MIT Center for Advanced Nuclear Energy Center the project entitled High Performance Fuel Design for Next Generation PWR’s presented the proposal of an internal and external cooled ring fuel with the objective of increasing the power density of a PWR reactor without compromising the safety margins of the installation. The thermal hydraulic conditions were calculated with the aid of the VIPRE subchannel code, which is a widely used tool in the analysis of nuclear reactor cores. STHIRP-1 is a subchannel code that has been developed at the Departamento de Engenharia Nuclear /UFMG. In order to evaluate the capacity of the STHIRP-1 program, mainly in relation to the thermal model, the new fuel concept was analyzed. The results were compared with those performed with the VIPRE code presented in the reference document.